Pathway of programmed cell death and oxidative stress induced by β-hydroxybutyrate in dairy cow abomasum smooth muscle cells and in mouse gastric smooth muscle. - Wulin Tian; Teng Wei; Bin Li; Zhe Wang; Naisheng Zhang; Guanghong Xie (PLoS ONE, 2014)
The administration of exogenous β-hydroxybutyrate (β-HB), as well as fasting and caloric restriction, is a condition associated with β-HB abundance and decreased appetite in animals. Increased β-HB and decreased appetite exist simultaneously in some diseases, such as bovine left displaced abomasums (LDA) and human chronic gastritis. However, the effects of β-HB on stomach injuries have not been explored. To elucidate the possible effects of exogenous β-HB on the stomach, mice were injected intraperitoneally with β-HB, and bovine abomasum smooth muscle cells (BSMCs) were treated with different concentrations of β-HB. We found that β-HB induced BSMCs endoplasmic reticulum- and mitochondria-mediated apoptotic cell death. β-HB promoted Bax expression and caspase-12, -9, and -3 activation while blocking Bcl-2 expression. β-HB also promoted AIF, EndoG release and p53 expression. β-HB acted on key molecules in the apoptotic cell death pathway and increased p38 and c-June NH2-terminal kinase phosphorylation while inhibiting ERK phosphorylation and PCNA expression. β-HB upregulated P27 and P21 mRNA levels while downregulating cyclin and CDK mRNA levels, arresting the cell cycle. These results suggest that BSMCs treated with β-HB can induce oxidative stress, which can be prevented by intracellular calcium chelators BAPTA/AM but not antioxidant NAC. Additionally, these results suggest that β-HB causes ROS generation through a Ca2+-dependent mechanism and that intracellular Ca2+ levels play a critical role in β-HB -induced apoptotic cell death. The impact of β-HB on programmed cell death and oxidative stress in vivo was confirmed in murine experiments. For the first time, we show oxidative stress effects of β-HB on smooth muscle. We propose that β-HB is a possible cause of some stomach diseases, including bovine LDA.